Perspectives for philosophy of the body and the new realism - А. К. Zhaparova (Омский научный вестник: Серия "Общество. История. Современность")
The article presents a commentary on the article by Mario Teodoro Ramirez «The Body by Itself. From the Phenomenology of the Body to an Ontology of the Embodied Self», in which he tries to declare an attempt to build a realism based on a correctly rethought philosophy of the body. It allows building a new type of realistic ontology of the embodied subject. Maurice Merleau-Ponty and Jean-Luc Nancy’s approaches to corporeality and flesh are seen by Ramirez as the most important steps in the so-called the ‘Corporal Turn’ and laying the conceptual foundation of the ontology of New Realism.